Peran Tradisi Grebeg Pancasila dalam Menanamkan Nilai Nasionalisme dan Karakter pada Generasi Muda di Blitar - Lutviana Riski; Suhartono Suhartono; Riki Suliana,R.S (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to examine how the Grebeg Pancasila tradition plays a role in instilling nationalistic values and character building for the younger generation in Blitar City. Grebeg Pancasila, which is routinely held every year, is a form of respect for Pancasila as the foundation of the state, as well as an educational medium in introducing national values to young people. This study uses a qualitative approach with data collection methods through in-depth interviews, participatory observation, and documentation. The informants in this study consisted of officers in the Bung Karno Tomb area, cultural officials, and a number of young people who participated in the series of Grebeg Pancasila activities. The results of the study show that this tradition makes a great contribution to fostering a sense of love for the homeland, strengthening a sense of unity, and building the character of the younger generation, especially in terms of discipline, responsibility, and a spirit of cooperation. Through activities such as cultural parades, joint prayers, various competitions, and community service, young people are trained to understand and practice the values of Pancasila in everyday life. These findings are expected to be input for local governments, communities, and related parties in efforts to preserve Grebeg Pancasila and develop similar activities that are more creative in instilling national values in the nation's next generation.